The effect of S/Mo ratio on structure and properties of MoSx-Ti composite coatings deposited by magnetron sputtering. (14th October 2020) - Wang, Tao; Xue, Chen; Yu, Shouming; Chen, Wei; Zhang, Guojun
Abstract: MoSx -Ti composite coatings with different S/Mo ratios were prepared by varying the substrate bias voltage of magnetron sputtering. It was found that the S/Mo ratio of the as-deposited MoSx -Ti coating decreased gradually from 1.7 to 1.3 as substrate bias voltage increased from −30 V to −110 V. The MoS1.7 -Ti coating exhibits a nanocrystalline and amorphous phase mixed structure while the other MoSx -Ti coatings were all amorphous structured. The hardness of the MoSx -Ti coatings increased from 8.8 GPa to 9.8 GPa as the S/Mo ratio decreased from 1.7 to 1.3. The MoSx -Ti coatings with the S/Mo above 1.4 exhibit COF with values smaller than 0.07 at RH of 50% and increased wear rate in the magnitude of ∼10 –7 mm 3 Nm −1 . The tribological behavior of the MoSx -Ti coatings were determined by the formation of the imperfect crystalline MoS2 tribofilm. With the decrease of the S/Mo ratio, the increased defects in imperfect crystalline MoS2 tribofilm lead to quicker consumption of the tribofilm during the trio-test, which result in a higher wear rate.